Development of Augmented Reality-Based Flipbook Media to Improve Children's Writing Skills - Noor Baiti Baiti; Uswatun Nisa; Suci Lestari (CV. Get Press Indonesia, 2024)
Porpuse this study to produce Flippbook media based on augmented reality for writing skill with materials that are adjusted to the age of kindergarten namely the Solar System. This Method research is a research and development (RnD). The model uses the Four-D (4-D) model which consists of four stages of development, namely Define, Design, Develop, Disseminate. Subject this research is children at TK ABA 1, 32 and 42 Banjarmasin. The instruments used are observation, expert and media expert validation checklists of skala likert and documentation. The results of this study state that the development of flipbook-based augmented reality media can be developed as a learning media aid for writing for children. The implication of this research is that it can be applied as a learning medium for children age 5-6 years at TK ABA 1,32 and 42 Banjarmasin in writing skills so that they can improve. The conclusion of this study is that the development of flipbook-based augmented reality media can build creativity, imagination and writing skills for children. Several unique and interesting images help children improve their writing skills.